Viktorianische Photographie : 1840-1890 - Pohlmann, Ulrich (Heidelberg : Edition Braus, 1993)
Adamson, Robert ; Anderson, James ; Annan, Thomas ; Bambridge, William ; Bedford, Francis ; Bourne, Samuel ; Cameron, Julia Margaret ; Carroll, Lewis ; Claudet, Antoine François Jean ; Clifford, Charles ; Cundall, Joseph ; Emerson, Peter Henry et al.
Viktorianische Photographie 1840-1890, Neuen Pinakothek, München, vom 26.2 bis 2.5.1993
boek